Telegram-Bot Applications in Drug Information Services and Pharmaceutical Counseling - Shelvia Lharas Anggitha; Ngesti Rahayu; Prasojo Pribadi; Setiyo Budi Santoso (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This article presents the development of a bot application to assist patients in obtaining drug information and counseling services from pharmacists. The draw.io network software was used to build a bot workflow. This study's findings include recommendations for bot workflows as well as examples of user interface designs.